(untitled) (Biological Sciences - PJSIR, 1998)
Free radical copolymerisation ofn-butyl acrylate (n-BA) and ethyl acrylate (EA) in methyl ethyl ketone MEK was accomplished at 60°C using BPO as initiator. It was observed that these monomers form copolymers in all monomeric ratios. Tensile properties and hardness were investigated for the poly blends prepared from chlori- nated rubber and n-BA-Co-EA. It was further observed that crosslinking density is increased with increase in the concentration of chlorinated rubber. Increase in crosslinking density appeared in the form of more tensile strength. Plasticizer and copolymer made the polyblends more soft and flexible. It is concluded that these blends may serve as good film forming materials.